Data Distribusi pada Jumlah Kasus Penyakit Tuberculosis (TBC) Wilayah Kabupaten/Kota di Jawa Barat pada periode 2016 hingga 2021 - Jasmin, Nur Shabrina; Rianto, Rianto; Purwayoga, Vega (Universitas Medan Area, 2024)
Tuberculosis (TB) or Mycobacterium Tuberculosis is a germ that causes Tuberculosis infection that is contagious and attacks anyone. It is still a public health problem in Indonesia. The number of TB cases in West Java is high with a total of 101,272 TB cases that continue to increase by 21.12% each year. Therefore, it is necessary to analyze the normality test on the data of the number of TB cases in West Java to determine whether the data comes from a population that has a normal distribution or not. The method used in this research uses a qualitative method by observing 'OPEN DATA JABAR